Pregnancy and the Postpartum Period in Women With Relapsing-Remitting Multiple Sclerosis Treated With Old and New Disease-Modifying Treatments: A Real-World Multicenter Experience - Zanghì, Aurora; D'Amico, Emanuele; Callari, Graziella; Chisari, Clara Grazia; Borriello, Giovanna; Grimaldi, Luigi Maria Edoardo; Patti, Francesco (Frontiers in Neurology, 2020)
Abstract Introduction: Trends of disease activity during pregnancy and post-partum period and until 24 months from the delivery, in the era of new drugs for the treatment of relapsing-remitting multiple sclerosis (RRMS) need to be investigated. Methods: In this cross-sectional Italian multicenter study, women with RRMS were included and it was considered the disease-modifying treatment (DMT) at the time of conception: interferons, glatiramer acetate, teriflunomide, dimethyl fumarate, fingolimod, natalizumab. The main outcome of the study was to determine the rate of relapse occurrence during pregnancy and postpartum in all women, grouped for every DMT. The secondary outcome was to determine the overall disease activity assessed by NEDA 3 (relapse, disability level and radiological activity) at 24 months from the date of delivery. Results: Completed data were available for 81 pregnancies (in 74 women). Women on interferons and glatiramer had longer disease duration than women on dimethyl fumarate, fingolimod, and natalizumab (p<.05). Overall, we recorded 25 relapses during pregnancy (11 in 11 women) and post-partum (14 in 14 women). Natalizumab was the most commonly DMT in women (3) who experienced relapses during pregnancy. IFNs were the most commonly prescribed DMT in women (8) who experienced relapses during post-partum. At multivariate analyses, specific treatment per se was not associated with relapse occurrence. No differences among the DMTs groups were recorded about NEDA 3 status at follow-up. Conclusions: In our population, there was no difference in terms of relapses occurrence, disability status and the overall disease activity during a follow up of 24 months.